Locating the Indo-Antarctica suture – Correlating the Rengali, Rauer and Ruker terranes in Gondwana - Gupta, Saibal; Chatterjee, Sandro; Arora, Devsamridhi; Bose, Subham; Dobe, Ritabrata (Polar Science, 2021)
The Rayner Complex of East Antarctica and the Eastern Ghats Province (EGP) of India are thought to have been contiguous in past supercontinents like Rodinia and Gondwana. These terranes have been correlated on the basis of similar granulite facies metamorphic imprints and isotopic age data that testify to Grenvillian (1100-900 Ma) and Pan-African (650-450 Ma) thermal signatures. The Grenvillian granulite facies metamorphic event is generally thought to represent collision between Antarctica and cratonic India, but the precise location of the Indo-Antarctic suture is disputed. The intensity of Pan-African age geological imprints is also variable in both continents, and their significance remains unclear. In this review, we correlate structural, metamorphic and geochronological data in both terranes and parts of their bounding cratons, and suggest that the Ruker Terrane and Rauer Group in Antarctica were continuous with the Rengali Province in India. Together with the established correlation between the EGP and the Rayner Complex, this implies that cratonic India along with the EGP-Rayner amalgam collided with the Archaean Ruker Terrane (part of the Crohn craton) at ~520 Ma along the southern Prince Charles Mountain in East Antarctica. This suture is distinct from the Grenvillian suture between EGP-Rayner and cratonic India. journal article